Effects of high-intensity interval training on biomarkers and inflammatory factors in patients with heart failure: a meta-analysis of randomized controlled trials - Zhang, Wanting; Hwang, Jooyeon; Lu, Beibei; Xu, Xin (Frontiers in Cardiovascular Medicine, 2025)
BackgroundThere is still controversy about the effect of high-intensity interval training (HIIT) on the levels of cardiac and inflammatory biomarkers in patients with heart failure compared with moderate-intensity continuous training (MCT) and conventional healthcare activities. This article is to systematically investigate the effects of HIIT on the levels of cardiac and inflammatory biomarkers in patients with heart failure compared with MCT and conventional healthcare activities.MethodsA computerized search of databases was conducted with the search year from the establishment of the database, and the screened results were subjected to quality assessment and data extraction, and the data was meta-analyzed using RevMan 5.4.1 software.Results11 randomized controlled trials (RCTs) were finally included (7 RCTs about BNP and NT-proBNP, 2 RCTs about inflammatory factors, and 2 RCTs involve both), containing a total of 904 study subjects, 457 in the observation group, and 447 in the control group. Meta-analysis showed that HIIT significantly reduced BNP and NT-proBNP levels in patients with heart failure compared with the control group (SMD = −1.33, 95% CI: −2.55∼−0.11, P = 0.03), while it had no significant effect on the level of CRP (SMD = −0.08, 95% CI: −0.33∼0.18, P = 0.56), TNF-α (MD = −0.11, 95% CI: −0.29∼0.08, P = 0.26), and IL-6 (MD = 0.3, 95% CI: −1.95∼2.55, P = 0.8).ConclusionsCompared with MCT and conventional healthcare activities, the implementation of HIIT in patients with heart failure can effectively reduce the levels of heart failure biomarkers and improve their health. However, the difference between HIIT and the control group was not significant in the regulation of inflammatory factors.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/#searchadvanced, PROSPERO CRD42024513099.